Globalization and Financial Market Contagion: Evidence from Financial Crisis and Natural Disasters - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
With financial globalization, investors can gain from diversification if returns from financial markets are stable and not correlated. However with volatility spillovers, increase in cross-market correlations exist as a real-effect and are not taken into account for asset allocation and portfolio composition. This chapter assesses financial contagion from two recent trends in the world economy: the global financial crisis and the 2011 Japanese natural disasters (tsunami, earthquake and nuclear crises).
Keywords: 330